Combinatorial Study of Lipid-like Materials for Gene Delivery. - Sun, Shuo. (2017)
Abstract: The evaluation of a library of lipidoids for in vitro DNA delivery through a facile combinatorial approach was investigated. The mild reactions between amines and acrylamides, acrylates, or epoxides enabled the construction of a library to screen for efficient gene delivery carriers. In Chapter 2, a combinatorial library of lipidoids was constructed and studied for in vitro gene delivery. The library of lipidoids was synthesized by reacting commercially available amines with lipophilic acrylates, acrylamides, or epoxides. Lipidoids derived from amine 86 (N,N-Bis(2-hydroxyethyl)ethylene diamine) and amine 87 (N-(3-aminopropyl)diethaneamine) showed high efficiency in DNA delivery, some with a higher transfection efficiency than Lipofectamine 2000, a commonly used commercial gold standard for in vitro gene delivery. The structure-activity relationship between the lipidoids was further studied with respect to small variations in chemical structures and the resulting efficiency in DNA delivery in vitro. Since these lipidoids are easy to synthesize and do not require a co-lipid for efficient DNA delivery, they could offer an inexpensive but effective alternative to other commonly used commercial gene delivery carriers. This Chapter 3 describes the synthesis of a combinatorial library of quaternized lipidoids and the evaluation of their abilities to facilitate in vitro DNA delivery. By formulating liposomes with a neutral helper lipid, 1, 2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), the quaternized lipidoids can significantly enhance their gene transfection abilities due to the weaken quaternized lipidoid and DNA binding and the hexagonal-phase forming propensity of liposomes. We further optimized the liposome composition and DNA dose for gene transfection and investigated the structure-activity relationships of the lipidoid library in DNA delivery.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Qiaobing Xu.; Committee: Qiaobing Xu, David Kaplan, and Kyongbum Lee.; Keyword: Chemical engineering.